The nurse's performance facing humanized care in urgency and emergency services: the challenges for implementation (Research, Society and Development, 2021)
Humanizing in health consists in recognizing the practices of professional and client interaction, through respect and trust, enabling a more dignified and fair reception for the patient. This study aimed to carry out an active search in the literature on the role of nurses in the face of humanized care in urgent and emergency services, as well as the challenges for its implementation. This is a descriptive study, with a qualitative methodological approach, using the Integrative Literature Review (RIL) as a technique, together with the PICO strategy to formulate the guiding question. This study was carried out between April and June 2021 in databases indexed within the Virtual Health Library (VHL): LILACS, BDENF and MEDLINE, by joining three Health Descriptors (DeCS) crossed with the Boolean operator “AND”: Emergency Nursing AND Nursing AND Humanization of Care, with 281 articles found in total. By adding the criteria for articles published in the last five years (2016 to 2021) in Portuguese and English, this number reduced to 124. After reading, analyzing and interpreting the research, 9 articles were selected. The humanization process within the urgency and emergency sector can be implemented, but in the long term, as long as the practices are put into practice, they are not just in the literature, through training in health teams, focusing on professionals who pass years in the same service, who end up getting used to the routine and often work in a cold manner. This study showed that nurses have a significant role in the care provided to patients in the emergency service.